Classroom assessment techinques : a handbook for college teachers - Angelo, Thomas; Cross, Patricia (San Francisco : Jossey bass, 1993)
How well are students learning? How effectively are faculty teaching? Teachers and tutors themselves are the closest observers of learning as it takes place in their classrooms and have the opportunity to become the most effective assessors and improvers of their own teaching. In order for teaching to improve, teachers and tutors must first be able to discover when they are off course, how far they are, and how to get back on the right track. Classroom Assessment Techniques provides a practical handbook to help teachers and tutors develop a better understanding of the learning process in their own classrooms and assess the impact of their teaching upon it. This resource offers teachers at all levels how-to advise on classroom assessment, including: * What classroom assessment entails and how it works * How to plan, implement, and analyse assessment projects * Twelve case studies that detail the real-life classroom experiences of teachers carrying out successful classroom assessment projects * Fifty classroom assessment techniques * Step-by-step procedures for administering the techniques * Practical advice on how to analyse your data.
Includes bibliographical references and index.
Keywords: Educational evaluation -- -- Handbooks, manuals, etc. -- United States; College teaching -- Handbooks, manuals, etc. -- United States; College students -- Case studies. -- Rating of -- United States